2020
DOI: 10.3389/fpubh.2020.589359
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety and Depression Among People Under the Nationwide Partial Lockdown in Vietnam

Abstract: This study aimed to evaluate the psychological effects of the partial lockdown on the people in Vietnam during the COVID-19 pandemic. An online questionnaire regarding attitudes toward COVID-19 along with psychological parameters, including the Impact of Event Scale-Revised (IES-R) Depression, Anxiety, Stress Scale-21 (DASS-21) was conducted. From a total of 1,382 questionnaires, the respondents reported low prevalence of depression (4.9%), anxiety (7.0%), and stress (3.4%). The mean DASS-21 scores recorded we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
168
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(190 citation statements)
references
References 24 publications
17
168
2
3
Order By: Relevance
“…This is in accordance with a global review which concluded a higher prevalence of psychological disorders among the general population (Xiong et al, 2020). Likewise, several other studies conducted in China, the Philippines and Vietnam also reported a significant impact on the mental health of people attributed to COVID-19 (Le et al, 2020;Tee et al, 2020;Wang, Pan, et al, 2020b). A majority of the participants rated their health as either "good" (n = 751, 47.0%) or "very good" (n = 649, 40.6%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with a global review which concluded a higher prevalence of psychological disorders among the general population (Xiong et al, 2020). Likewise, several other studies conducted in China, the Philippines and Vietnam also reported a significant impact on the mental health of people attributed to COVID-19 (Le et al, 2020;Tee et al, 2020;Wang, Pan, et al, 2020b). A majority of the participants rated their health as either "good" (n = 751, 47.0%) or "very good" (n = 649, 40.6%).…”
Section: Discussionsupporting
confidence: 91%
“…The scores of these subscales were grouped into five categories, namely "normal," "mild," "moderate," "severe" and "extremely severe," as shown in Table 1. DASS was also used in previous studies conducted in China, Vietnam and the Philippines, which investigated the psychological impact of the COVID-19 outbreak (Le et al, 2020;Tee et al, 2020;Wang, Pan, et al, 2020b) (McAlonan et al, 2007. Additionally, the DASS-21 reported excellent validity among Pakistani samples (Aslam & Kamal, 2019;Chishti & Rafiq, 2019).…”
Section: Survey Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…(33) University students who suffered a family economic downturn and had family members with chronic illnesses reported lower QoL scores. This is consistent with findings from other studies in China and Vietnam (30,34). Loss of economic income implies difficulty in accessing treatment, medication and living expenses, affecting quality of life (29,30,35).…”
Section: Discussionsupporting
confidence: 94%
“…The IES-R and DASS-21 were used in the following COVID-19 studies in various countries: Vietnam, Philippines, China and Poland (Le, Dang, et al, 2020 ; Le, Lai, et al, 2020 ; Tee, Tee, et al, 2020 ; Wang, Chudzicka-Czupała, Grabowski, Pan, Adamus, Wan, et al, 2020 ; Wang, Pan, Wan, Tan, Xu, McIntyre, et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%